The Contributions of Near Work and Outdoor Activity to the Correlation Between Siblings in the Collaborative Longitudinal Evaluation of Ethnicity and Refractive Error (CLEERE) Study - Jones-Jordan, Lisa A.; Sinnott, Loraine T.; Graham, Nicholas D.; Cotter, Susan A.; Kleinstein, Robert N.; Manny, Ruth E.; Mutti, Donald O.; Twelker, J. Daniel; Zadnik, Karla (Investigative ophthalmology & visual science, 2014)
We determined the correlation between sibling refractive errors adjusted for shared and unique environmental factors using data from the Collaborative Longitudinal Evaluation of Ethnicity and Refractive Error (CLEERE) Study. Refractive error from subjects' last study visits was used to estimate the intraclass correlation coefficient (ICC) between siblings. The correlation models used environmental factors (diopter-hours and outdoor/sports activity) assessed annually from parents by survey to adjust for shared and unique environmental exposures when estimating the heritability of refractive error (2*ICC). Data from 700 families contributed to the between-sibling correlation for spherical equivalent refractive error. The mean age of the children at the last visit was 13.3 ± 0.90 years. Siblings engaged in similar amounts of near and outdoor activities (correlations ranged from 0.40-0.76). The ICC for spherical equivalent, controlling for age, sex, ethnicity, and site was 0.367 (95% confidence interval [CI] = 0.304, 0.420), with an estimated heritability of no more than 0.733. After controlling for these variables, and near and outdoor/sports activities, the resulting ICC was 0.364 (95% CI = 0.304, 0.420; estimated heritability no more than 0.728, 95% CI = 0.608, 0.850). The ICCs did not differ significantly between male-female and single sex pairs. Adjusting for shared family and unique, child-specific environmental factors only reduced the estimate of refractive error correlation between siblings by 0.5%. Consistent with a lack of association between myopia progression and either near work or outdoor/sports activity, substantial common environmental exposures had little effect on this correlation. Genetic effects appear to have the major role in determining the similarity of refractive error between siblings.